Decision importance and Black and Hispanic jurors’ judgments of outgroup and ingroup defendants in a trial simulation - Leippe, Michael R. (Psychology, crime & law, 2022)
Because they involve important decisions, should actual trials involve less or more discrimination than trial simulations? Does discrimination occur when defendant and juror both belong to underprivileged groups? In two experiments employing a 2 (decision importance) X 2 (defendant ingroup/outgroup status) design, Black and Hispanic (and some White) college students read a robbery/murder trial transcript. The defendant belonged to participants’ racial/ethnic group or one of the others. Low-decision-importance instructions asked mock-jurors to consider the case carefully. High-decision-importance instructions emphasized the study was a government-sponsored assessment of jurors’ reasoning about a real trial with known guilt/innocence. In Experiment 1 (n = 118), outgroup discrimination – judging outgroup defendants more likely guilty – was evident only under high importance. In Experiment 2 (n = 135), which presented weaker prosecution of the trial and included processing-motivation measures, outgroup discrimination occurred regardless of importance. Black and Hispanic mock-jurors discriminated against defendants of the other group. Greater identity-related processing motivation was reported under high importance. High importance may reduce bias associated with heuristic processing, but promote bias through processing infused with evaluative associations involving social identity and race/ethnicity. The defendant outgroup discrimination regardless of importance suggests prejudice observed in trial simulations may generalize to actual trials.